Interoceptive Awareness and Suicidal Ideation in a Clinical Eating Disorder Sample: The Role of Body Trust. Issue 5 (September 2021) - Perry, Taylor R.; Wierenga, Christina E.; Kaye, Walter H.; Brown, Tiffany A.
Highlights: Suicidality in eating disorders (ED) is linked to low interoceptive awareness (IA). Low body trust predicted the presence of suicidal ideation in an ED sample. No dimensions of IA were associated with severity of suicidal ideation. Abstract: Previous research has demonstrated that both suicidal ideation (SI) and eating disorders (EDs) are associated with poor interoceptive awareness (IA). Suicidality research has demonstrated that the IA dimension of lower body trust is associated with SI, suicide plans, and suicide attempts. Similarly, in ED samples, recent research supports that low body trust has been the most robust dimension of IA associated with eating pathology. However, to date, research is lacking in how dimensions of IA may be associated with SI in an ED sample, above and beyond the impact of eating pathology on SI. Thus, in a clinical ED sample, the present study sought to determine which IA dimensions predict the presence and severity of SI, above and beyond ED symptoms. Participants ( N = 102) completed a clinical interview assessing SI and self-report assessments including the Multidimensional Assessment of Interoceptive Awareness (MAIA). Results demonstrated that patients with current SI reported greater ED psychopathology, lower MAIA Attention Regulation, MAIA Self-Regulation, and MAIA Trusting scores compared to patients without SI. Higher ED psychopathology and lower MAIA Attention Regulation, Self-Regulation, and Trusting subscale scores were all significantly associated with the presence of SI. However, only low MAIA Trusting scores predicted the presence of SI, above and beyond covariates (age, depression, and eating pathology). No MAIA subscales were correlated with the severity of SI. Consistent with previous research, results suggest low MAIA Trusting scores may be associated with SI in ED samples and highlight the need for future research on mechanisms of these associations.